Investigation of Anisotropic Behavior and Statistical Evolution of Acoustic Emission Energy during the Deformation of Layered Sandstone - Shujian Li; Shaobin Dong; Binting Cai; Menglai Wang; Yanhong Xie; Jingguo Luo (Geofluids)
To further understand the anisotropic behavior of layered rock and the precursor characteristics of rock mass instability, a series of uniaxial compression experiments using a loading system and an acoustic emission system was conducted on sandstone specimens. The influence of bedding on the mechanical parameters and failure modes and the statistical evolution of the acoustic emission energy were successively discussed. The results of axial stress-strain curves and crack propagation modes showed that the existence of a bedding plane increased the anisotropy of the rocks, and the magnitude of the bedding inclination also exerted certain influence on this anisotropy. Furthermore, we used the least squares method and the maximum likelihood method to analyze the b value and power-law exponent, respectively. The results of statistical evolution of acoustic emission energy showed that the b value, the effective power-law exponent, and the optimal exponent could be used as monitoring indexes for the rock mass stability. With the progress of the experiment, the following phenomena pertaining to acoustic emission activities occurred, which may indicate imminent danger of collapse: (1) the crackling noises increased significantly; (2) the variation of the b value exhibited a significant downward trend; and (3) the effective power-law exponent and the optimal exponent changed in different stages and gradually decreased as the final failure was approached. The findings in this paper may provide a theoretical basis for predicting the collapse and instability of rock mass structures.